Digital Multimodal Composing in EFL Grammar Instruction:Exploring Pre-Service Teachers' Experiences and Perspectives - Sadikin, Irma Savitri; Apsari, Yanuarti (Universitas Pendidikan Mandalika, 2025)
The growing integration of Digital Multimodal Composing (DMC) in English as a Foreign Language (EFL) instruction has transformed conventional grammar teaching methods by incorporating text, images, sound, and movement. However, limited empirical research explores its application in grammar instruction, particularly from the perspective of pre-service teachers. Guided by Liang and Lim (2020) DMC pedagogical framework, grounded in Systemic Functional Linguistics and Design Thinking, this study examines the implementation of DMC in an Indonesian EFL higher education context. Fifteen pre-service teachers from an English Language Education Program participated in the study. Data were collected using a case study design through classroom observations, semi-structured interviews, and student reflections. Findings indicate that DMC fosters engagement, enhances conceptual understanding, and develops digital literacy skills. High-achieving students demonstrated strong digital fluency, creativity, and analytical skills in integrating multimodal elements into grammar lessons. Conversely, low-achieving students faced challenges with multimodal cohesion, tool navigation, and troubleshooting technical issues. The study highlights the importance of explicit instruction, guided practice, and peer collaboration in supporting students' multimodal literacy development. It emphasizes the need for structured pedagogical scaffolding to effectively integrate DMC into EFL grammar instruction. The findings suggest that while DMC promotes student-centered and multimodal learning, sustained instructional support and curriculum integration are essential for its success.